Sequence and directivity in cardiac muscle injury of COVID-19 patients: an observational study - Wang, Yixuan; Chen, Jianxiong; Jin, Lin; Wu, Lingheng; Zhang, Mengjiao; Sun, Jiali; Shen, Cuiqin; Du, Lianfang; Wang, Bei; Li, Zhaojun (Frontiers in Cardiovascular Medicine, 2023)
Objective To compare cardiac function indicators between mild and moderate to severe COVID-19 patients and to try to identify the sequence and directivity in cardiac muscle injury of COVID-19 patients. Methods From December 2022 to January 2023, all patients with laboratory-confirmed SARS-CoV-2 infection in Shanghai General Hospital Jiading Branch were enrolled. The clinical classification was stratified into mild, moderate, or severe groups. We collected the clinical and laboratory information, transthoracic echocardiographic and speckle-tracking echocardiographic parameters of patients and compared the differences among different groups. Results The values of echocardiographic parameters in mild group were lower than that in moderate or severe group (P < 0.05) except LVEF. The values of LVEF of mild and moderate group were higher than severe group (P < 0.05). There were no significant differences between moderate and severe group. Positive correlations were observed between left ventricular global longitudinal strain (LVGLS) and myoglobin (r = 0.72), E/e' and age (r = 0.79), E/e' and BNP (r = 0.67). The multivariate analysis shows that SpO2 (OR = 0.360, P = 0.02), LVGLS (OR = 3.196, P = 0.003) and E/e' (OR = 1.307, P = 0.036) were the independent risk factors for mild cases progressing to moderate or severe. According to the receiver operating characteristic (ROC) curves, when all the COVID-19 patients was taken as the sample size, the area under the curve (AUC) of the LVGLS was the highest (AUC = 0.861). The AUC of the LVGLS was higher than LVGCS (AUC = 0.565, P < 0.001). Conclusion When mild COVID-19 progresses to moderate or severe, both systolic and diastolic functions of the heart are impaired. LVGLS was the independent risk factor for mild cases progressing to moderate or severe cases. Longitudinal changes may manifest earlier than circumferential changes as myocardial disease progresses in COVID-19.